A Revival Study of Existing Technology for Sugarcane Plantation Registration System with Special Reference to Solapur District - Mhetre, Dayanand; Gulavani, Sampada (International Journal of Computer Sciences and Engineering, 2025)
The world’s business environment has become volatile today. The industrial sectors have been struggling to make their mask. All manufacturing industries have been battling for their survival. In India agricultural sector too seems lying on death bed due to adverse weather conditions, less rainfalls, apathy of farmers and other numerous reasons. Sugar industry is one of the most important agro-based industries in India and ranks second amongst major agro-based industries. The sugar industry is not an exception it has been observed that sugar industries in India have been practicing old traditional methods and systems for even procuring sugarcane the essential raw material for production of sugar. There are infinite reasons for the gloomy picture of sugar industries in India. This industry faces many problems as short-margin, persistent losses in sugar recovery and losses in the sugar manufacturing due to old machinery and lack of new technology for producing of sugar. The registration system of sugarcane itself has many loopholes and needs to be upgraded. Thus the researcher has concentrated his whole study on methods, systems & technologies used by sugar industry today and the inbuilt lacuna in whole process and also want to upgrade whole process by this research, by finding out problems in registration system